Pengetahuan Ibu tentang Pijat Bayi pada Anak Usia 0-12 Bulan Secara Mandiri - Fathia Fakhri Inayati Said (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to describe the mother's knowledge about self-massage for babies aged 0-12 months at the Semar Clinic, Hamadi Jayapura Village. This type of research is quantitative descriptive with a cross-sectional approach. The study's results described the mother's knowledge about self-massage for babies aged 0-12 months. As many as 17 people (56.7%) had good knowledge, 13 people (43.3%) had sufficient knowledge, and no respondents had less knowledge. In conclusion, the description of mothers' knowledge about infant massage independently at the Semar Clinic, Hamadi Jayapura Village, is mainly in the excellent knowledge category. Keywords: Knowledge, Infant Massage